Development of Teaching Materials Based on Local Wisdom Using the PQ4R Method to Improve Reading Comprehension in Grade 5 Students at SDN Panyirapan - Firly Istiqomah; Aceng Hasani; Odien Rosidin (Global READ Center, 2025)
This study was prompted by the observed low reading comprehension skills among fifth-grade students. The objective was to develop digital teaching materials based on local wisdom, specifically Banten folk tales, by applying the PQ4R (Preview, Question, Read, Reflect, Recite, and Review) method to improve reading comprehension skills. The research method used was Research and Development with the ADDIE development model, which consists of the stages of analysis, design, development, implementation, and evaluation. Data collection techniques included observation, interviews, and tests (pretest and posttest). The results of the study showed that the developed digital teaching materials were highly suitable for use and received very positive responses from students, with an average response questionnaire score of 90%. The effectiveness of the teaching materials was proven through improved student learning outcomes, with an N-Gain score of 0.71, which falls into the high category. Digital teaching materials based on local wisdom (Banten folk tales) using the PQ4R method proved to be effective, engaging, and relevant for improving students' reading comprehension.